The effect of the process temperature on the bondability in diffusion bonding of AISI 430 with nodular cast iron - Taskin, Mustafa; Ozan, Sermin; Kolukisa, Sedat (Carl Hanser Verlag, 2006)
The effect of process temperature on the bondability of stainless steel AISI 430 and nodular cast iron was studied. The diffusion bonding was investigated experimentally under a protective atmosphere at various temperatures and a prescribed constant pressure blow which would cause macro-deformation. Microstructure examinations were carried out with the help of optical microscopy, SEM and EDS. Hardness values were measured by HV scale under a load of 200 g. At the bond interface cross section, decarburized and dechromised regions were observed on the ductile cast iron side and the stainless steel side respectively. Best mechanical and metallurgical properties were observed for the specimen bonded at 1100 degrees C process temperature at 15 MPa, for 20 min. As a function of the process temperature elevation, an increase of graphite atoms, migrating towards the interface, and a reduction of graphite atoms at the nodular graphite diameters was noticed.
Die auswirkung der prozesstemperatur auf die fügbarkeit beim diffusionsbonden von rostfreiem ferritischen stahl des typs AISI 430 mit sphärogusseisen